Pengaruh Variasi Putaran Benda Kerja Dan Putaran Tool Menggunakan Metode Pemakanan Tangensial Pada Proses Turn-Milling Terhadap Kekasaran Permukaan - Jefryanto, Gusmardani; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The surface roughness of a machining process is a very important factor in the field of production that is one of the turn-milling process. Turn-milling is a combined machining process of turning and milling with complete tools (cutting) where workpieces and tools rotate together. The turn-milling process can generally be categorized in orthogonal turn-milling, tangential turn-milling and co-axial turn-milling methods. The resulting surface quality is also affected by the parameters of the machining process in the form of rotation of the workpiece and the rotation of the tool. The purpose of this research is to know the effect of parameters on surface roughness and optimal parameter to surface roughness by doing tangential process of turn-milling. By varying the parameter variables, the surface roughness generated in this study is influenced by the rotation of the workpiece and the rotation of the tool. The higher the tool rotation the lower the surface roughness. Conversely, the higher the rotation of the workpiece the higher the surface roughness. The optimal parameter is a rotation tool of 25000 rpm with a rotation of 630 rpm objects found in the roughness class N7 with a roughness value of 1.321 Î¼m where the roughness value is lower among other N7 roughness classes.Keywords : Turn-milling, Tangential Turn-milling, Rotation, Roughness.